2006
DOI: 10.7205/milmed.171.11.1083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sociodemographic Characteristics, Illness Process, and Social Support on the Levels of Perceived Quality of Life in Veterans

Abstract: Quality of life is a broad, complex, multidimensional concept incorporating psychological, sociopsychological, economic, philosophical, social, cultural, and spiritual dimensions. As accompanying or even constituting the concept of quality life, social support (empathic, informational, instrumental, and reassurance support) has not been studied. This study sought to determine the effects of sociodemographic characteristics, illness process, and type of social support on the quality of life levels of veterans h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Social support from family, friends, and other servicemembers played an integral role in CR of injured servicemembers, similar to findings of previous studies regarding the connection between social support and quality of life [30], social support and suicide prevention [13], and preference toward mental health services utilizing family-based interventions [14]. The results of this study also support the social benefits and sense of camaraderie associated with participation in adapted sports and recreation among injured servicemembers [15][16].…”
Section: Discussionsupporting
confidence: 88%
“…Social support from family, friends, and other servicemembers played an integral role in CR of injured servicemembers, similar to findings of previous studies regarding the connection between social support and quality of life [30], social support and suicide prevention [13], and preference toward mental health services utilizing family-based interventions [14]. The results of this study also support the social benefits and sense of camaraderie associated with participation in adapted sports and recreation among injured servicemembers [15][16].…”
Section: Discussionsupporting
confidence: 88%
“…While some research has focused on the coping strategies, quality-of-life aspects, and psychosocial adaptation occurring after the onset of an injury or amputation in the context of war disability (e.g., Abrams, 1990;Aflakseir, 2010;Desmond & MacLachlan, 2006;Yazicioglu et al, 2006), very limited research has been conducted on PTG in veterans with combat-related limb amputations (Benetato, 2011;Phelps et al, 2008). But more importantly, no research has been found focusing on the relationship between coping strategies and PTG in veterans with limb amputations.…”
Section: Study Aimsmentioning
confidence: 99%
“…It is considered that there exists a linear relationship between increasing age and increasing hopelessness level (Karataş, Karataş, & Şenol, 1989). In a few studies conducted with disabled veterans in Turkey, no relation between age and quality of life are found (Başcıllar, 2017;Yazicioglu, Duyan, Karatas, & Özgül, 2006). It was found that young people who had active services in the military and who had disabled veterans had higher levels of depression and hopelessness than the older disabled veterans (Green, Grace, Lindy, Glesser, & Leonard, 1999;Hankin, Spiro III, Miller, & Kazis, 1999).…”
Section: Discussionmentioning
confidence: 99%